Organizational Capabilities Driving Business Performance: Resource Based View Theory - Syamsudin Syamsudin; Aflit Nuryulia Praswati; Nelly Purnama Sari; Sri Murwanti (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The performance of MSMEs has become the center of attention in almost every government. This is based on the high contribution of MSMEs to the economy of a region. However, it cannot be denied that MSMEs still have weaknesses that need to be improved so that they can sustain their business in a sustainable manner. Organizational capability as a company resource is a driving factor for the performance of MSMEs. This study uses the theoretical basis of Resource Based View to examine the performance of MSMEs through market communication capability, pricing capability and product innovation capability. Methods of data collection using a questionnaire using google form media. The number of respondents' answers that can be analyzed is 85 respondents. The results of data analysis using SmartPLS, namely product innovation capability and pricing capability, have a significant positive effect on performance and also have a significant positive effect when mediating the effect of market communication capability on performance, but the results of this study also show that market communication capability does not have a significant positive effect on performance.